Unveiling Transcendental Symbols in the Rejang Ayunan Tradition of Pupuan, Tabanan - I Gusti Made Andrian Sumantri (Bali Tourism Journal, 2024)
The Rejang Ayunan Dance tradition is one of the rituals conducted during the full moon ceremony (Purnama Kapat) in the Piodalan Ceremony at Puseh temple, Bale Agung Village, Pupuan Sub-district, Tabanan Regency, Bali. This tradition involves a group of male dancers, ranging from children to unmarried individuals, performing en masse. The Rejang Ayunan Dance is a ceremonial dance specifically intended for ritual purposes, particularly the Dewa Yadnya ceremony. According to the belief of the people of Pupuan Village, failure to perform the Rejang Ayunan Dance may result in crop failure, pest infestation, and disease outbreaks. The tradition of Rejang Ayunan Dance has been passed down from one generation to the next and plays a significant role in the social, cultural, and religious life of the Pupuan Village community. However, the existence of this tradition faces challenges from the influences of modernization, urbanization, and changing cultural preferences. The influence of mass media and popular culture can also reduce the interest of the community, especially the younger generation, in learning and practicing this tradition. To address these challenges, the Pupuan Village community needs to strengthen their commitment to preserving this tradition. Steps that can be taken include raising awareness of the value and beauty of the tradition through appropriate education and promotion, actively involving the younger generation in traditional activities, strengthening intergenerational communication, and obtaining financial support and resources from various parties concerned with the preservation of local culture.